2021
DOI: 10.1186/s12978-021-01265-x
|View full text |Cite
|
Sign up to set email alerts
|

Continuum of maternity care among rural women in Ethiopia: does place and frequency of antenatal care visit matter?

Abstract: Introduction The ministry of health (MOH) of Ethiopia recommends 4 or more focused antenatal care (ANC) visits at health centre (HC) or at a higher level of health facility (HF). In Ethiopia, few studies investigated time dimension of maternal health continuum of care but lack data regarding place dimension and its effect on continuum of care. The aim of this study is to estimate effect of place of ANC-1 visit and adherence to MOH’s recommendations of MOH for ANC visits on continuum of care rur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 27 publications
4
15
2
Order By: Relevance
“…The study found that the overall magnitude of the completion of the continuum of maternity care was 12.9% (95%CI: 11.1 – 14.9%). This result was in line with studies done in Ethiopia (13.9%) [ 31 ], Nigeria (11.7%) [ 44 ], and Sub-Saharan Africa (13.6%) [ 45 ]. However, the finding was higher than studies done in Ethiopia, for instance, Arbaminch (9.7%) [ 46 ] and EDHS 2016 (6.56%) [ 28 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The study found that the overall magnitude of the completion of the continuum of maternity care was 12.9% (95%CI: 11.1 – 14.9%). This result was in line with studies done in Ethiopia (13.9%) [ 31 ], Nigeria (11.7%) [ 44 ], and Sub-Saharan Africa (13.6%) [ 45 ]. However, the finding was higher than studies done in Ethiopia, for instance, Arbaminch (9.7%) [ 46 ] and EDHS 2016 (6.56%) [ 28 ].…”
Section: Discussionsupporting
confidence: 91%
“…Previously studies done in Ethiopia identified that the completion of continuum of maternity care was impending by different factors like age [ 31 ], place of residence [ 31 33 ], educational status [ 31 34 ], marital status [ 28 ], religion [ 28 ], wealth status [ 28 ], parity [ 28 ], birth order [ 28 , 33 , 35 ], sex of household head [ 27 ], contraceptive use [ 33 ], being informed on pregnancy complications/danger signs during pregnancy [ 28 , 31 , 34 ], distance to health facilities [ 28 , 31 , 33 ], knowledge on the continuum of care [ 33 ], media exposure [ 28 , 32 ], woman’s decision making power [ 31 , 33 ], exposed to health extension program [ 31 ], pregnancy-related complication [ 31 ], timing of first initiation of ANC [ 31 , 34 ], and number of ANC visits [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Participants who had been told about pregnancy complications are 2.73 times more likely to complete the maternity continuum of care as compared with those who had not been told about pregnancy complications. The finding of this study is conclusive to the previous study stated as the odds of completion of the maternity continuum of care were higher among women informed about danger signs/pregnancy complications ( 22 , 25 ). The possible explanation could be due to the health-seeking behavior of women with information about pregnancy complications might be higher compared with those with no information ( 38 ) and this makes them conscious to fully engage across the continuum of care.…”
Section: Discussionsupporting
confidence: 87%
“…This might inflate the prevalence compared with the current study, as education is one factor significantly associated with the outcome variables. On the other hand, the current study finds a higher prevalence compared with the previous study done at Arbaminch Ethiopia 9.5% ( 24 ), in Ethiopia from EDHS data analysis 13% ( 16 ), in rural women Ethiopia 13.9% ( 25 ), Nigeria 18% ( 26 ), Ghana 8% ( 27 ), and Tanzania 10% ( 28 ). The possible explanation for the higher prevalence of completion of the maternity continuum of care compared with the previous study done in Ethiopia might be due to the variation in the demarcation of the operational definition of the outcome variable.…”
Section: Discussioncontrasting
confidence: 69%
“…Similarly, mothers whose husbands were aged between 40 and 49 years were three times more likely to drop out of the PNC than those aged between 20 and 29 years. A National Health Extension Program assessment in Ethiopia showed that increasing age was negatively associated with the continuum of maternity care ( 25 ). Similarly, a community-based cross-sectional study in East Gojjam reported that being in the age range of 15–24 years increases the odds of early initiation and continuation of ANC visits ( 26 ).…”
Section: Discussionmentioning
confidence: 99%